Autophagy unleashes noncanonical microRNA functions. Issue 12 (1st December 2020) - Santovito, Donato; Egea, Virginia; Bidzhekov, Kiril; Natarelli, Lucia; Mourão, André; Blanchet, Xavier; Wichapong, Kanin; Aslani, Maria; Brunßen, Coy; Horckmans, Michael; Hristov, Michael; Geerlof, Arie; et al.
ABSTRACT: MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression which act by guiding AGO (argonaute) proteins to target RNA transcripts in the RNA-induced silencing complex (RISC). This macromolecular complex includes multiple additional components ( e.g ., TNRC6A) that allow for interaction with enzymes mediating inhibition of translation or RNA decay. However, miRNAs also reside in low-molecular weight complexes without being engaged in target repression, and their function in this context is largely unknown. Our recent findings show that endothelial cells exposed to protective high-shear stress or MTORC inhibition activate the macroautophagy/autophagy machinery to sustain viability by promoting differential trafficking of MIR126 strands and by enabling unconventional features of MIR126-5p . Whereas MIR126-3p is degraded upon autophagy activation, MIR126-5p interacts with the RNA-binding protein MEX3A to form a ternary complex with AGO2. This complex forms on the autophagosomal surface and facilitates its nuclear localization. Once in the nucleus, MIR126-5p dissociates from AGO2 and establishes aptamer-like interactions with the effector CASP3 (caspase 3). The binding to MIR126-5p prevents dimerization and proper active site formation of CASP3, thus inhibiting proteolytic activity and limiting apoptosis. Disrupting this pathway in vivo by genetic deletion of Mex3a or by specific deficiency of endothelial autophagy aggravates endothelial apoptosis and exacerbates the progression of atherosclerosis. The direct inhibition of CASP3 by MIR126-5p reveals a non-canonical mechanism by which miRNAs can modulate protein function and mediate the autophagy-apoptosis crosstalk.